THE INFLUENCE OF PERSON ORGANIZATIONAL FIT (PO FIT) AND COMPENSATION ON OCB (ORGANIZATION CITIZENSHIP BEHAVIOR) WITH MODERATION OF ORGANIZATIONAL CULTURE - Anik Susilowati; Hasan Abdul Rozak (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to analyze the effect of person organizational fit and compensation on organizational citizenship behavior with moderating organizational culture. The population in this study were civil servants in the Bendan regional public hospital, Pekalongan City, totaling 155 employees. The sampling method used was the purposive sampling method. The data analysis technique used moderation regression analysis using SPSS software. The results showed that Person Organization Fit and compensation have a significant positive effect on Organizational Citizenship Behavior. Organizational culture moderates the effect of Person Organization Fit and compensation on Organizational Citizenship Behavior. Keywords: Person organization fit, compensation, organizational culture, organizational citizenship behavior